Colour Removal from Dye Wastewater Using Sugar Cane Dust as an Adsorbent - S.D. Khattri; M.K. Singh (Adsorption Science & Technology)
Decolouration of dilute solutions of basic dye stuff was carried out using sugar cane dust as an adsorbent. It was found that low adsorbate concentration, small particle size of the adsorbent, a temperature of 25°C and a pH value of 7.5 for the medium all favour the removal of dye from aqueous solutions. The percentage of dye adsorbed by sugar cane dust decreased from 96.48% to 83.32% and from 90.78% to 78.02% for Malachite Green and Methylene Blue, respectively, when the concentration of the dye was increased from 6 mg/l to 12 mg/l. Similarly, the adsorption of Crystal Violet and of Rhodamine B also decreased with increasing dye concentration in the solutions. The amount of dye (Malachite Green and Rhodamine B) adsorbed decreased from 3.04 mg/g to 2.57 mg/g and from 2.53 mg/g to 2.17 mg/g when the temperature of the solution was increased from 25°C to 45°C, indicating that the process was exothermic. The values of the adsorption capacity (Q 0 ) of Malachite Green and Rhodamine B on the adsorbent varied from 4.87 to 4.08 and from 4.26 to 3.82, respectively, as the temperature increased from 25°C to 45°C. The equilibrium data obey the requirements of the Langmuir adsorption model, demonstrating the formation of a monolayer of dye molecules on the outer surface of the adsorbent. The variation in the extent of removal with pH has been explained on the basis of surface ionisation and complexation. Various thermodynamic parameters (ΔG 0 , ΔH 0 and ΔS 0 ) have also been determined in order to explain the results.